Improvement of Tar Removal Performance in Biomass Gasification Using Fixed-Bed Biomass Filtration - Hafif Dafiqurrohman; Dadan Kosasih; Arief Wildhan Naro Putra; Muhammad Ismail Bagus Setyawan; Adi Surjosatyo (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Several studies have proven the efficiency of gasification as a thermal process in terms of material decomposition and chemical energy. Synthetic gas (syngas) is a gasification product that can be used as an energy source. However, it needs to undergo treatment to remove the tar content, which could cause several issues in the combustion system. Tar removal can be conducted through biomass filters. In this study, three types of filters were investigated: biochar, rice straw, and rice husk filters. Three thicknesses of the porous media (30, 40, and 50 cm) were investigated. The results revealed that porous media thickness significantly affects tar removal efficiency, as the efficiency was found to increase with the thickness. Biochar was proven to be the best filter media among the three types, with a tar removal efficiency of 59.45% at a thickness of 50 cm.